1969
DOI: 10.1063/1.1652690
|View full text |Cite
|
Sign up to set email alerts
|

Direct Video Imaging of X-Ray Topographs

Abstract: In this paper, a video display system for direct imaging of transmission and reflection x-ray topographs of Si and GaAs wafers is described. This system allows instantaneous viewing of x-ray topographs with fields of view on the order of 2 cm by 1 cm. The resolution of the system is now limited by the sensitivity of the x-ray phosphor to about 30 μ. Slip bands and diffused devices have been directly observed in both Si and GaAs, as have been accidentally induced damage such as scratches and wafer warpage. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1971
1971
1977
1977

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Many authors have reported systems based on X-ray sensitive vidicons (Chikawa & Fujimoto, 1968), conventional television with phosphor screens, sometimes with image intensifiers interposed (Meieran, Landre & O'Hara, 1969;Lang & Reifsnider, 1909;Kozaki, Hashizume & Kohra, 1972) and charge sensitive diode arrays (Rozgonyi, Haszko & Statile, 1970). With conventional sources these authors reported exposure times between 0.5 s and one minute with resolutions in the range from 10/~m to 30/zm over areas of a few mm square.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported systems based on X-ray sensitive vidicons (Chikawa & Fujimoto, 1968), conventional television with phosphor screens, sometimes with image intensifiers interposed (Meieran, Landre & O'Hara, 1969;Lang & Reifsnider, 1909;Kozaki, Hashizume & Kohra, 1972) and charge sensitive diode arrays (Rozgonyi, Haszko & Statile, 1970). With conventional sources these authors reported exposure times between 0.5 s and one minute with resolutions in the range from 10/~m to 30/zm over areas of a few mm square.…”
Section: Introductionmentioning
confidence: 99%
“…This was Papers 155 and 156 presented at the Cleveland, Ohio, Meeting of the Society, Oct. [3][4][5][6][7] 1971.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Tubes such as the SEC vidicon, or the orthacon with a single state intensifier added in front, are used to process and display the image on a monitor (5,6). Such devices usually have less resolution (of the order of 30-50~) and medium sensitivity to x-rays.…”
mentioning
confidence: 99%
“…I n the past few years several systems have been reported for the direct viening of X-ray topographic images [l to 5 ) . Two of them rely on converting the X-rays to electrical signals by means of a n X-ray vidicon, where either a lead oxide (PbO) 111 or silicon diode array [ 2 ] is used as the target. I n the othci.…”
Section: Introductionmentioning
confidence: 99%